Cut to the chase – How multimodal cohesion secures narrative orientation in film trailers. (December 2021) - Hoffmann, Christian R.
Highlights: Examines the cohesive thrust of opening shots in different film trailer genres. Identifies highly frequent lexical expressions (and semantic domains) in film trailers. Illustrates how multimodal patterns form genre-specific cohesive links. Shows how semiotic patterns maximize the effective cognitive uptake of information. Abstract: Recent years have seen a growing number of studies explore the narrative, persuasive and multimodal design of film trailers (Maier, 2009, 2011; Wildfeuer and Pollaroli, 2017 ). While such work has primarily looked at the ways in which trailers realize persuasive functions (Hediger, 2001; Maier, 2011 ; Krebs, 2020 ), this paper examines how the (audio-visual) representational choices made by trailer editors can provide narrative orientation for the film audience. Inside a self-compiled corpus of 150 genre-stratified US-American film trailers, recurring audio-visual, cohesive patterns are elicited. It will be shown that the visual effects of this cohesive thrust can be tied to the cinematographic choices editors make in the opening shots of the trailer, by using specific shot scales, (types of) settings and (non-)human represented participants. To capture the verbal dynamics of trailer cohesion, the study explores the key semantic domains to which all lexical expressions in the trailer dialogues can be linked (Rayson et al., 2004 ). Results of this study confirm that both visual and verbal elements form recurring genre-specific patterns. They unleash their multimodal potential of film trailers by tapping into the previous (genre) knowledge of trailer audiences, facilitating the cognitive uptake of audiovisual information for the audience as the trailer unfolds.